Degradation of ciprofloxacin by peroxymonosulfate activation using catalyst derived from spent lithium-ion batteries. (15th August 2022) - Zhao, Yanlan; Wang, Hou; Ji, Jingqin; Li, Xiaodong; Yuan, Xingzhong; Jiang, Longbo; Yang, Jinjuan; Shao, Yanan; Guan, Xian
Abstract: The recovery and reuse of anode materials from spent lithium-ion batteries has attracted increasing attention. This study provides a strategy for the high-value utilization of waste anode materials. Two kinds of catalysts containing different graphite C content were prepared by a calcination process using the anode material of spent lithium-ion batteries. The synthesized AM (AM-450/AM-850) catalysts were applied to activate peroxymonosulfate and degrade ciprofloxacin in water. The AM catalysts consist of CuO and graphite C, which can effectively activate peroxymonosulfate. Under optimal conditions (ciprofloxacin = 10 mg/L; catalyst = 0.4 g/L; [peroxymonosulfate] = 1.0 mM), the degradation efficiencies of AM-450 and AM-850 for ciprofloxacin were 90% and 84% separately within 60 min. Both radical pathways (SO4 · −, HO· and · O2 − ) and non-radical pathways ( 1 O2, surface electron transfer) participated in the degradation of ciprofloxacin in AM-450/PMS and AM-850/PMS systems with a noticeable difference. The surface electron transfer non-radical channel was the main channel for ciprofloxacin degradation in AM-450/PMS, while the radical degradation channel played a crucial role in AM-850/PMS system. This work presented a novel insight into the peroxymonosulfate heterogeneous activation mechanism with the use of spent lithium-ion batteries derived-catalyst. Graphical abstract: Image 1 Highlights: A high-value utilization strategy for the waste anode materials was developed. The catalysts derived from anode scraps are cost-effective and easy to prepare. The catalytic activity is comparable with that prepared from pure chemicals. Reveal the mechanism of ciprofloxacin degradation catalyzed by the catalysts. The removal of pollutant by charge transfer was faster than free radical pathway.